Exploring Blood Donation: Perspectives among Undergraduate Students in Peshawar, Pakistan: Blood Donation Perceptions in Peshawar Undergraduates - Zahir, Salman; Khan, Khansa; Atif, Muhammad; Khan, Wisal; Khan, Haseeb; Khan, Imad; Mazhar, Somia; Shah, Jamal (Pakistan BioMedical Journal, 2024)
To improve voluntary donation and public health in the face of Pakistan's shifting regulations and challenges, it is crucial to comprehend the blood donation patterns of undergraduate students in Peshawar. Objective: To compare and assess undergraduate students in medical, allied health sciences, and non-medical fields in Peshawar, Pakistan, on their knowledge, attitudes, barriers to, and motivations for, blood donation. Methods: An eight-month observational cross-sectional study with 1232 undergraduate students from various academic fields was conducted. Participants were assessed through a comprehensive questionnaire regarding blood donation. Data were analyzed using SPSS version 27.0, employing descriptive statistics and the chi-square test. Results: The study enrolled 1232 undergraduate students, with 65.2% male and 34.6% female participants. Among them, 82.3% were aware of their blood group. While 24.74% exhibited poor knowledge about blood donation, 62.98% demonstrated moderate knowledge, and 12.29% had good knowledge. Additionally, 39.9% had never donated blood, but 83.9% expressed willingness to donate in the future. Fear of needles (13.90%), fear of infection (13.20%), and medical unfitness (13.10%) were significant barriers, while motivations included saving lives (22.20%), helping friends and family (19.40%), and moral obligation (14.80%). Conclusions: The study concluded that undergraduate students in Peshawar possess a moderate level of understanding regarding blood donation, with medical students showing higher knowledge levels. Despite variations across disciplines, positive attitudes towards donation were common, indicating potential for increased voluntary donation